Femmes aux yeux ouverts Women with open eyes / un film de Anne Laure Folly ; produit par Amanou Production. - Folly, Anne-Laure (California Newsreel, 1994)
Surveys social conditions faced by women in Burkina Faso, Mali, Senegal and Benin, including circumcision, forced marriage, AIDS, and economic repression. Examines grass-roots efforts toward education and improvement as Africa opens to democracy.
Originally produced in Togo.
Keywords: Women -- Africa, Sub-Saharan -- Economic conditions.; Women -- Africa, Sub-Saharan -- Social conditions.; Female genital mutilation.; Marriage customs and rites -- Africa, Sub-Saharan.; AIDS (Disease) -- Africa, Sub-Saharan.; Women -- Diseases -- Africa, Sub-Saharan.; Women -- Africa, West -- Social conditions.; Feminism -- Africa, West.; Women -- Burkina Faso.; Women -- Mali.; Women -- Senegal.; Women -- Benin.; Sexually transmitted diseases -- Africa, West.; Clitoridectomy -- Africa, West.; Infibulation -- Africa, West.; Businesswomen -- Africa, West.; Africa, West -- Social conditions.; Documentary films.